2019
DOI: 10.3390/v11060554
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Infections among Patients with Acute Febrile Jaundice in Burkina Faso

Abstract: Hepatitis E virus infection is a significant public health problem in many parts of the world including Africa. We tested serum samples from 900 patients in Burkina Faso presenting with febrile icterus. They all tested negative for yellow fever, but those from 23/900 (2.6%) patients contained markers of acute HEV infection (anti-HEV IgM and HEV RNA positive). Genotyping indicated that 14 of the strains were HEV genotype 2b. There was an overall HEV IgG seroprevalence of 18.2% (164/900). In a bivariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…The phylogenetic analysis also showed one strain that belongs to genotype 2 subtype b that is closely related (~90-93% of identity) to strains isolated from an outbreak in Nigeria in 2017 [23], in France from a person with history of recent travel to Senegal [24], and during a recent outbreak in Burkina Faso (Fig. 3) [25]. Of note, this strain is highly related to the strain isolated in 2008 in the CAR (100% of identity) [11].…”
Section: Phylogenetic Analysismentioning
confidence: 86%
“…The phylogenetic analysis also showed one strain that belongs to genotype 2 subtype b that is closely related (~90-93% of identity) to strains isolated from an outbreak in Nigeria in 2017 [23], in France from a person with history of recent travel to Senegal [24], and during a recent outbreak in Burkina Faso (Fig. 3) [25]. Of note, this strain is highly related to the strain isolated in 2008 in the CAR (100% of identity) [11].…”
Section: Phylogenetic Analysismentioning
confidence: 86%
“…In Burkina Faso, HEV is likely endemic in humans and in swine [ 7 8 9 ]. Although HEV genotyping in acute jaundice human patients between 2013 and 2016 exclusively identified genotype 2 [ 10 ], zoonotic genotype 3 is circulating in swine in Burkina Faso [ 7 ], as in other African countries [ 11 12 13 ]. The higher seroprevalence in people with occupational exposure to pigs (76.0% pork butchers in Ouagadougou [ 7 ]) compared to the general population in Burkina Faso (39.0% in blood donors [ 9 ]) and in Nigeria [ 14 ] suggests the potential importance of zoonotic infections on the continent, at least in certain risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…Other similar studies have shown that HEV IgM seroprevalence is generally between 0-34% in sub-Saharan Africa [17]. The HEV IgM rates detected in other endemic countries were 2.6% in Burkina Faso [18], 10.4% in the Demographic Republic of Congo [12], 38.4% in Niger [19], 22% in Cameroon [20], 0.34% in Algeria [21], and 4.4% in Sudan [22].…”
Section: Discussionmentioning
confidence: 72%